Pemikiran Pendidikan Ki Hajar Dewantara dan Implikasinya terhadap Penyelenggaraan Pendidikan di Tingkat SMP - Eutik Suhendar; Didi Sunardiana; Ubun Ubun; Ricky Yoseptry (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
This study aims to conduct an in-depth analysis of Ki Hajar Dewantara’s ideas on emancipatory education and to identify their implications for the education system at the junior secondary level (Sekolah Menengah Pertama). Amid the implementation of the Kurikulum Merdeka and the various challenges of twenty-first-century education, Ki Hajar Dewantara’s educational philosophy has regained relevance as a foundation for transforming learning practices. This study employs a library research method with a qualitative–narrative approach. The primary data are derived from the works of Ki Hajar Dewantara, while secondary data come from books, academic journals, and policy documents related to national education and the Kurikulum Merdeka. The findings indicate that emancipatory education according to Ki Hajar Dewantara is a process of “guiding” all of a child’s innate potentials through the among system, which is grounded in the principles of asih (care), asah (intellectual development), and asuh (nurturing). Education is directed toward enabling learners to attain the highest possible levels of safety and happiness as individuals and as members of society, emphasizing a balanced development of cipta (thought), rasa (feeling), karsa (will), and pekerti (character). In the context of junior secondary schools, these ideas call for a paradigm shift from teacher-centered and exam-oriented learning toward student-centered, contextual, and differentiated learning that integrates character strengthening. Teachers assume the role of pamong by applying the educational trilogy Ing Ngarso Sung Tulodo, Ing Madyo Mangun Karso, and Tut Wuri Handayani. The practical implications are reflected in curriculum design, pedagogical practices, and holistic assessment oriented toward the development of the Profil Pelajar Pancasila.